Development, Validity, and Acceptability of Android-based Applications in Ecology: A Technology Acceptance Model (TAM) Approach - Astaño, Jereme Lleva (Bumi Publikasi Nusantara, 2025)
This study aimed to develop, validate, and evaluate the acceptability of Android applications in teaching ecology. Three interactive applications were created using a developmental research approach with AppsGeyser, a free platform for building educational Android apps. These applications (the Learning Guide App, Word Search App, and Quiz Game App) were aligned with the Grade 7 Science Curriculum content standards of the Department of Education in the Philippines. A quantitative approach was employed to assess the apps and evaluate their acceptability through a survey using the constructs from the Technology Acceptance Model (TAM). The applications were examined for content, instructional, and technical quality, with evaluators reporting high validity across all factors. Results showed that user feedback indicated strong agreement with the perceived usefulness (PU) and behavioral intention to use (BIU) of the applications. Additionally, respondents demonstrated general acceptability of perceived ease of use (PEOU) and attitude towards the use (ATU) of Android applications. Overall, the study demonstrates the potential of developed Android-based applications as effective and accessible learning tools for enhancing ecology education.